Efforts to Increase Awareness of Human Rights Among Youth - Adila, Nur; Putri, Sandy Auliya; Syawalia, Tasya; Helmi, Niko; Nasrullah, Muhammad; Susanti, Emilia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Human rights issues among adolescents in Indonesia have a variety of problems, including cases of bullying, discrimination, brawls, and sexual harassment. A person or group of people who are guaranteed by the law and do not get or are feared will not get a fair and correct legal settlement based on the applicable legal mechanism (Article 1, point 6 of Law No. 39 of 1999 concerning Human Rights). The purpose of this research is to find out about the implementation of human rights and efforts to address problems in the world of teenagers. The research was conducted at Sultan Syarif Kasim Riau State Islamic University. The research method used is qualitative research involving data collection techniques through in-depth interviews and literature studies. Based on the results of in-depth interviews with several students of the Sultan Syarif Kasim Riau State Islamic University, the Geography Education Study Programme revealed that everyone must be given education about self-preservation and education in order to understand how precarious the abuse cases that are rampant in the world of enagers are. So that we can be more vigilant and emphasise more about sex education to everyone, especially teenagers.